Using environmental impact assessment and post‐construction monitoring data to inform wind energy developments. Issue 2 (24th February 2015) - Zwart, Mieke C.; Robson, Peter; Rankin, Sarah; Whittingham, Mark J.; McGowan, Philip J. K.
Abstract : Ecological data are routinely collected for Environmental Impact Assessments (EIAs) and post‐consent planning requirements to assess potential negative impacts of developments on wildlife. Such data are almost always obtained from a single site and this often prohibits robust statistical analysis due to insufficient replication. Here, we integrate data collected during EIAs and post‐construction monitoring from multiple sites to study the impact of wind energy developments on the distribution and abundance of black grouse. We show that the construction of wind turbines at these seven sites had no detectable effect on the abundance of lekking black grouse, but that leks within 500 m of the nearest planned wind turbine moved locally after construction (median distance before construction was 250 m and after was 803 m). This effect was not observed for leks greater than 500 m from a wind turbine. Although not examined within this study, there are several reasons which, individually or in combination, could underlie the localized movement of black grouse we report. These include the operation of the wind energy development, volume of visitors, changes in land management both within and surrounding the site, and habitat enhancement measures designed to attract black grouse to specific areas away from the wind energy development. We demonstrate that ecological data routinely collected by EIAs and post‐construction surveys from multiple projects can be combined to provide a robust ecological evidence base on which to inform development decisions. We recommend that easily‐accessible data repositories be maintained by regulatory authorities to enable the development of a robust ecological evidence base to guide planning decisions across a wide range of different wildlife.